UPAYA MENINGKATKAN ANTUSIASME PEMUDA DALAM PEMBANGUNAN PEMERINTAHAN DESA MEKARBAKTI KABUPATEN SUMEDANG - Rohman, Abdul; Sunendar, Iman (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The development of village governance in Indonesia often faces challenges in youth participation. In Mekarbakti Village, despite the significant number of young people, their participation in village development activities is still minimal. It is due to time constraints, as many young people work in the industrial sector, and there is a lack of facilities to support youth activities. This research aims to analyse the enthusiasm of youth in village Government development and explore efforts that can increase their participation. The method employed utilizes a descriptive qualitative approach, including deep conversations with community leaders and adolescents of Mekarbakti Village, in addition to a comparison to Linggar Village, Bandung Regency, and effectively raised young excitement. The research results show that although the Mekarbakti Village Government has formed a Karang Taruna, youth participation is still limited. Compared to Linggar Village, which engages youth through open Employee Performance and an entrepreneurial approach, Mekarbakti Village needs to adopt a similar approach to increase youth enthusiasm.